Cathelicidin levels in nasal secretions are associated with the severity of acute bronchiolitis. Issue 6 (13th March 2021) - Papadaki, Maria; Marmarinos, Antonios; Tsolia, Maria; Gourgiotis, Dimitrios; Soldatou, Alexandra
Abstract: Objective: To investigate the association of serum vitamin D and nasal secretion antimicrobial peptides (AMPs) levels with the severity of acute bronchiolitis. Study design: We conducted a prospective single pediatric tertiary care center cohort study of inpatients aged 0–18 months with a first episode of acute bronchiolitis from November 1st 2014 to April 30th 2017. Disease severity was determined by the length of hospitalization and supplemental hospital data. Qualitative measurements included serum 25(OH)D and nasal secretion LL‐37 and β‐defensin‐2 levels. Correlations were examined with the Mann–Whitney and Kruskal–Wallis criteria for qualitative and the correlation coefficient Spearman's rho for quantitative factors. Multiple linear and logarithmic regression were performed to adjust for confounding factors. Results: The study population consisted of 153 infants and toddlers with median age 3.1 months (interquartile range:1.6–4.9). No association was found between serum 25(OH)D and AMPs nasal secretions levels. Serum 25(OH)D and nasal secretion β‐defensin‐2 levels were not associated with the severity of bronchiolitis. In contrast, LL‐37 levels were inversely associated with the length of hospitalization (rho = −0.340, p = .001), the need for medication use ( p = .001), as well as the duration of oxygen supplementation (rho = −0.339, p = .001), and intravenous fluid administration (rho = −0.323, p = .001). This association remained significant after adjustment for potential confounders. Conclusion: A significant association between LL‐37 nasal secretions levels with the severity of acute bronchiolitis was found in hospitalized infants and toddlers. The role of LL‐37 in the pathogenesis of bronchiolitis merits further investigation.